Alkylation modified pistachio shell-based biochar to promote the adsorption of VOCs in high humidity environment. (15th February 2022) - Cheng, Tangying; Li, Jinjin; Ma, Xiuwei; Zhou, Lei; Wu, Hao; Yang, Linjun
Abstract: The objective of this work was to evaluate the adsorption capacity of alkylated modified porous biochar prepared by esterification and etherification (PSAC-2) for low concentrate volatile organic compounds (VOCs, toluene and ethyl acetate) in high humidity environment by experiments and theoretical calculations. Results showed that PSAC-2 has a large specific surface area and weak surface polarity, at 80% relative humidity, its capacities for toluene and ethyl acetate adsorption could be maintained at 92% and 87% of the initial capacities (169.9 mg/g and 96.77 mg/g). The adsorption behaviors of toluene, ethyl acetate, and water vapor were studied by adsorption isotherms, and isosteric heat was obtained. The desorption activation energy was obtained by temperature programmed desorption experiment. The outcomes manifested that the PSAC-2 can achieve strong adsorption performance for weakly polar molecules. Through density functional theory (DFT) simulations, owing to the interaction of hydrogen bonds, oxygen-containing groups became a significant factor influencing the adsorption of VOCs in humid environments. These results could provide an important reference for VOCs control in a high humidity environment. Graphical abstract: Image 1 Highlights: Pistachio shells were converted to biochar, and modified with ethanol and NaHSO4 . Alkylation significant increased biochar's adsorption for VOCs under humid environment. Oxygen-containing functional groups promote the adsorption of VOCs. Hydroxyl and carboxyl affect water vapor adsorption on biochar through hydrogen bonding.